Research progress of indoleamine 2, 3-dioxygenase inhibitors. (February 2015) - Jiang, Tianze; Sun, Yingying; Yin, Zhichao; Feng, Sen; Sun, Liping; Li, Zhiyu
Indoleamine 2, 3-dioxygenase (IDO, subsequently named IDO1) can degrade the level of essential amino acid tryptophan in mammals, and catalyze the initial and rate-limiting step through the kynurenine pathway. Broad evidence implies that IDO is overexpressed in both tumor cells and antigen-presenting cells, facilitating the escape of malignant tumors from immune surveillance. In the past decades, the inhibition of IDO has been one of the most promising areas in cancer immunotherapy and many potential inhibitors of IDO have been designed, synthesized and evaluated, among whichd -1-methyl-tryptophan and INCB24360 have advanced to clinical trial stage. This review aims to give an overview of the rationale for IDO as a therapeutic target as well as the research progress of IDO inhibitors.